Art, History, and Anachronic Intervenctions Since 1990 - Kernbauer, Eva (2021)
This book examines contemporary artistic practices since 1990 that engage with, depict, and conceptualize history, arguing that art offers fruitful strategies for creating historical consciousness and perspectives for political agency. The analytical instrument of anachrony comes to the fore as an experimental method, as will (para)fiction, counterfactual history, testimonies, ghosts and spectres of the past, utopia, and the "juridification" of history.